“Go Home and Sin No More!” Reimagining Faith that Changes the Lives of Offenders to New Narratives of Rebirth and Transformation - Mashau, Thinandavha Derrick (2023)
The justice system in South Africa used prisons as punitive instruments before the dawn of democracy. New developments focus mainly on restorative justice that seeks to rehabilitate, reintegrate, and restore offenders to their communities. This system has allowed space for chaplaincy and spiritual work in South African incarceration centers. This article uses the missional reading of John 8:1–11 and the narrative of David Heritage to demonstrate that faith, not religion, can change ex-offenders’ lives into narratives of rebirth and transformation. Ex-offenders are given a second opportunity to serve the missio Dei as agents of missional conversion and transformation.
Keywords: spiritual work; Chaplaincy; Prison Ministry; Transformation; Conversion; Mission; Religion; Faith